Exposure to brominated flame retardants in utero and through lactation delays the development of DMBA-induced mammary cancer: potential effects on subtypes? - Juarez, Melany N.; McDermott, Alec; Wade, Michael G.; Plante, Isabelle (Frontiers in Endocrinology, 2024)
Introduction Brominated flame retardants (BFRs) are chemical compounds used to reduce the flammability of various products; some BFRs exhibit endocrine-disrupting properties and can leach into the environment leading to human and wildlife exposure. The mammary gland has specific vulnerability windows during which it is more sensitive to the effects of endocrine disrupting compounds (EDCs), such as the in utero life, puberty and pregnancy. Our previous studies revealed precocious mammary gland development, disruptions in junctional proteins, and altered proliferation-apoptosis balance during puberty in rats exposed to BFRs in utero and through lactation. Such effects have been associated with increased mammary cancer risk. Objective The current study aimed to determine if in utero and lactational exposure to BFRs renders the mammary gland more susceptible to 7,12-dimethylbenz[a]anthracene (DMBA)-induced mammary cancer. Methods Dams were exposed to a BFRs mixture (0. 0.06 or 60 mg/kg/day), and mammary cancer was induced in pups using DMBA at post-natal day 46. Tumors onset and growth were monitored, and tumors were characterized using histology and molecular biology. Results Although BFRs exposure did not significantly affect mammary tumor number or burden, it showed significant delay in mammary tumor onset and growth in BFR-exposed animal. These effects could potentially be due to BFRs' impact on cellular responses, DMBA metabolism, or mammary gland shift of the sensitivity window. Molecular analysis of mammary tumors showed a shift in the ratio of luminal A, luminal B, and (HER2)-enriched tumors, and an increase in triple-negative breast cancer (TNBC) subtypes in BFR-exposed animals. Additionally, BFRs exposure showed lung lesions indicative of inflammation, independent of mammary cancer development. Conclusion Our study highlights the complex relationship between BFRs exposure and mammary cancer risk, emphasizing the need for further investigation into underlying mechanisms and long-term effects of BFRs on mammary gland development and carcinogenesis.